Plant organ growth: stopping under stress - Maizel, Alexis (Current biology, 2016)
Summary Plant organs reproducibly reach a set size and shape, and a key question is what prevents overgrowth. A new study uses imaging and computer modelling of the Arabidopsis sepal to show that mechanics determines growth arrest and thus final organ shape.